Lifetime Risks of Alzheimer’s Disease Dementia Using Biomarkers for Preclinical Disease - Brookmeyer, Ron (Alzheimers Dement, 2018)
INTRODUCTION: Lifetime risks are the probabilities of progressing to AD dementia during ones’ lifespan. Here we report the first estimates of the lifetime and ten-year risks of AD dementia that account for age, gender and biomarker tests for preclinical disease. METHODS: We used a multistate model for the disease process together with U.S. death rates. RESULTS: Lifetime risks of AD dementia vary considerably by age, gender and the pre-clinical or clinical disease state of the individual. For example, the lifetime risks for a female with only amyloidosis are 8.4% for a 90 year old and 29.3% for a 65 year old. Persons younger than age 85 with mild cognitive impairment, amyloidosis and neurodegeneration have lifetime risks of AD dementia greater than 50%. DISCUSSION: Most persons with preclinical AD will not develop AD dementia during their lifetimes. Lifetime risks help interpret the clinical significance of biomarker screening tests for AD.